2018
DOI: 10.7197/223.vi.431429
|View full text |Cite
|
Sign up to set email alerts
|

INVESTIGATION OF THE RELATIONSHIP BETWEEN Β2-Adrenergic RECEPTOR (Β2-Ar) POLYMORPHISM AND GASTRİC CANCER

Abstract: Gastric cancer is a multifunctional disease. Emotional stress, physiological and neuroendocrine changes in cancer patients can lead to the activation of the hypothalamic-pituitary-adrenal axis and the release of hormone dependent hormones such as catecholamine. In particular, it has been reported that catecholamine induction directly affects the biological behavior of tumor cells via β2-Adrenergic receptor (β2-AR) mediated signaling. In this study, it was aimed to investigate polymorphism of β2-AR gene (rs1042… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…20 The current understanding of genetic polymorphism and GC development is largely based on studies conducted in Asian and Caucasian populations. 21 Many studies have revealed that GC risk is associated with polymorphisms in genes involved in DNA synthesis and repair, inflammatory response, metabolic enzymes, and oxidative damage. 22 Human miRNA biogenesis is processed inside the nuclues and cytoplasm as a step wise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The current understanding of genetic polymorphism and GC development is largely based on studies conducted in Asian and Caucasian populations. 21 Many studies have revealed that GC risk is associated with polymorphisms in genes involved in DNA synthesis and repair, inflammatory response, metabolic enzymes, and oxidative damage. 22 Human miRNA biogenesis is processed inside the nuclues and cytoplasm as a step wise.…”
Section: Discussionmentioning
confidence: 99%
“…This result agreement with the previous report done by scholars. 21 Beside to this, GC patients and control subjects were evaluated by logistic regression analysis for smoking habits. No statistically significant difference was identified between GC patients and smoking habits in the Turkish population investigated in the current study (p=0.201, Table 3).…”
Section: Discussionmentioning
confidence: 99%